157k views
0 votes
Multiply Conjugates




(r+1/4)r-1/4)

User Rawrex
by
5.4k points

2 Answers

0 votes


(a+b)(a-b)=a^2-b^2


\left(r+(1)/(4)\right)\left(r-(1)/(4)\right)=r^2-(1)/(16)

User Tristan Tao
by
4.9k points
5 votes

Answer:


\large\boxed{\left(r+(1)/(4)\right)\left(r-(1)/(4)\right)=r^2-(1)/(16)}

Explanation:


\text{Use}\ (a+b)(a-b)=a^2-b^2\\\\\left(r+(1)/(4)\right)\left(r-(1)/(4)\right)=r^2-\left((1)/(4)\right)^2=r^2-(1^2)/(4^2)=r^2-(1)/(16)

User Jpwatts
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.